Gamma-polyglutamic acid electrostatic compound as well as preparation method and application thereof

By combining γ-polyglutamic acid with positively charged antibacterial surfactant, an electrostatic complex was formed, and an efficient antibacterial coating was prepared, which solved the in-hospital infection problems caused by medical devices during use, and realized the device Stable binding of the surface and excellent antibacterial effect.

CN119386284APending Publication Date: 2025-02-07CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES

Patent Information

Application Number
CN202411551412.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Existing medical devices are prone to inducing in-hospital infections during use, especially long-term indwelling devices, which can easily lead to bacterial colonization and biofilm formation, increasing the risk of surgical failure and drug resistance problems.

Method used

By combining gamma-polyglutamic acid with a positively charged antibacterial surfactant to form an electrostatic complex, a coating that can bind to the substrate and has high antibacterial properties was prepared.

Benefits of technology

The γ-polyglutamic acid electrostatic composite coating not only has excellent broad-spectrum antibacterial properties, but can evenly cover the surface of medical devices of different substrates and shapes, combine them to stabilize, extend the service life of the device, and solve the internal and external cavity of complex devices. Problems of stable surface coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005115179680000011
    Figure HDA0005115179680000011
  • Figure HDA0005115179680000012
    Figure HDA0005115179680000012
  • Figure HDA0005115179680000021
    Figure HDA0005115179680000021
Patent Text Reader

Abstract

The invention provides a gamma-polyglutamic acid electrostatic compound. The gamma-polyglutamic acid electrostatic compound is formed by compounding gamma-polyglutamic acid and an antibacterial surfactant with positive charges. Compared with the prior art, the gamma-polyglutamic acid electrostatic compound provided by the invention is constructed through electrostatic interaction, not only has good cell compatibility and blood compatibility, but also has excellent broad-spectrum antibacterial property, can be uniformly coated on the surfaces of medical instruments with different base materials, shapes and sizes, is stable in combination, and can be applied to medical instruments with different shapes and sizes. The coating process has universality and is suitable for solving the problem of pollution of current medical instruments, prolonging the service life of the medical instruments and solving the problem of coating stability of the surfaces of inner and outer cavities of complex instruments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of medical devices, and in particular relates to a gamma-polyglutamic acid electrostatic complex, a preparation method and application thereof. Background Art

[0002] The use of implantable or interventional medical devices is often accompanied by the risk of hospital-acquired infection, which may be caused by cross-contamination, inadequate instrument disinfection, environmental problems, untimely care, etc. Uncontrollable medical device contamination increases the risk of surgical failure and may require secondary surgery for debridement, increasing the patient's pain and treatment costs. In severe cases, it may cause sepsis and other problems, and face the threat of death. Especially for medical devices that require long-term intervention or implantation in the body, hospital-acquired infection problems greatly reduce their service life and limit their scope of use. It is reported that the proportion of urinary tract infections caused by long-term indwelling catheters is as high as more than 50%, and bloodstream infections caused by central venous catheters account for 30%. Studies have shown that after bacteria colonize on the surface of medical devices, they can gradually aggregate and multiply to form biofilms, which is one of the main causes of device contamination.

[0003] At present, in the face of infection problems caused by device contamination, antibiotics are usually used in clinical practice. However, the high frequency use of antibiotics will cause drug resistance, which has attracted great attention from the World Health Organization. From a material perspective, modifying medical devices to give them the ability to reduce bacterial colonization, kill pathogenic microorganisms or inhibit biofilm formation is a recognized alternative solution that can minimize the use of drugs. Common medical device surface modification methods include bulk raw material blending, device surface chemical grafting, swelling and impregnation, and physical coating. Among them, the coating method has a simple process flow and a wide range of applications, so it has received widespread attention.

[0004] A Chinese patent with publication number CN107854733B discloses an intelligent antibacterial coating and a preparation method thereof, which uses 2-(pyridin-2-yldisulfanyl)ethane-1-amine hydrochloride (PDA) and dopamine hydrochloride (DA) to modify γ-polyglutamic acid, further dissolves the modified γ-polyglutamic acid and an organic antibacterial agent in an organic solvent, prepares colloidal particles loaded with the antibacterial agent by a selective solvent method and disperses them in ethanol, and finally uses electrophoretic deposition technology to prepare an antibacterial coating on the surface of a medical implant metal material. Although the method described herein imparts good antibacterial properties to medical devices, the preparation process of the colloidal particles is complicated, methods such as electrophoretic deposition are costly, and process optimization is difficult, and there are disadvantages in practical applications.

[0005] A Chinese patent with publication number CN117442787A discloses a lubricating antibacterial drug-loaded coating on the surface of a medical catheter, and a preparation method and application thereof. The coating utilizes ternary polymerization of a hydrophilic monomer, a guanidine-containing monomer, and a photosensitive monomer, followed by a Schiff base reaction for drug loading, and constructs a lubricating antibacterial drug-loaded coating on the surface of the device by ultraviolet light curing. However, the photocuring method is difficult to construct a coating in the inner cavity of the catheter, and the scope of application is severely restricted, and the degree of optimization of the device is limited. Summary of the invention

[0006] In view of this, the technical problem to be solved by the present invention is to provide a γ-polyglutamic acid electrostatic complex that is stably bonded to a substrate and has high antibacterial properties, and a preparation method and application thereof.

[0007] The invention provides a gamma-polyglutamic acid electrostatic complex, which is formed by compounding gamma-polyglutamic acid and a positively charged antibacterial surfactant.

[0008] Preferably, the molecular weight of the γ-polyglutamic acid is 10,000 to 2,000,000 Daltons;

[0009] The positively charged antibacterial surfactant is selected from one or more of lauroyl arginine ethyl ester hydrochloride, polyhexamethylene biguanide hydrochloride, octadecyl dimethyl benzyl ammonium chloride, hexadecyl trimethyl ammonium chloride and tetradecyl trimethyl ammonium chloride.

[0010] Preferably, the mass ratio of the γ-polyglutamic acid to the positively charged antibacterial surfactant is 1:1 to 1:5.

[0011] The present invention also provides a method for preparing a γ-polyglutamic acid electrostatic complex, comprising the following steps:

[0012] S1) providing an aqueous solution of γ-polyglutamic acid;

[0013] providing an aqueous solution of a positively charged antimicrobial surfactant;

[0014] S2) under stirring, adding dropwise an aqueous solution of a positively charged antibacterial surfactant into an aqueous solution of γ-polyglutamic acid to obtain a precipitate;

[0015] S3) freeze-drying the precipitate to obtain the γ-polyglutamic acid electrostatic complex.

[0016] Preferably, the concentration of γ-polyglutamic acid in the aqueous solution of γ-polyglutamic acid is 0.01 to 0.15 g / mL;

[0017] The concentration of the positively charged antibacterial surfactant in the aqueous solution of the positively charged antibacterial surfactant is 0.01 to 0.15 g / mL.

[0018] Preferably, the stirring speed is 150 to 500 rpm; the dripping speed of the aqueous solution of the positively charged antibacterial surfactant is 10 to 100 mL / min; and the stirring is continued for 10 to 40 min after the dripping of the aqueous solution of the positively charged antibacterial surfactant is completed.

[0019] Preferably, the precipitate is washed with water by centrifugation and then freeze-dried; the centrifugal speed is 3000-8000 rpm.

[0020] The present invention also provides an antibacterial coating, comprising the above-mentioned gamma-polyglutamic acid electrostatic complex.

[0021] The present invention also provides a method for preparing an antibacterial coating, comprising the following steps:

[0022] S1) dissolving the γ-polyglutamic acid electrostatic complex described in any one of claims 1 to 3 or the γ-polyglutamic acid electrostatic complex prepared by any one of the preparation methods of claims 4 to 7 in an organic solvent to obtain a coating solution;

[0023] S2) coating the coating solution into a film to obtain an antibacterial coating.

[0024] Preferably, the organic solvent is selected from one or more of ethanol, methanol and dimethyl sulfoxide;

[0025] The concentration of the gamma-polyglutamic acid electrostatic complex in the coating solution is 0.01-0.1 g / mL.

[0026] The present invention provides a γ-polyglutamic acid electrostatic complex, which is formed by compounding γ-polyglutamic acid and a positively charged antibacterial surfactant. Compared with the prior art, the γ-polyglutamic acid electrostatic complex provided by the present invention is constructed through electrostatic interaction, and not only has good cell compatibility and blood compatibility, but also has excellent broad-spectrum antibacterial properties, and can be evenly coated on the surface of medical devices of different substrates, shapes and sizes, combined with stability, and the coating process has universality, which is suitable for solving the current medical device pollution problem, extending its service life, and solving the problem of stable coating on the inner and outer cavity surfaces of complex devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a graph showing the hemolysis rate test results of the γ-polyglutamic acid electrostatic composite antibacterial coating medical catheter obtained in Examples 1 to 6 of the present invention;

[0028] Figure 2 This is a diagram showing the cell compatibility test results of the γ-polyglutamic acid electrostatic composite antibacterial coating medical catheter obtained in Examples 1 to 6 of the present invention;

[0029] Figure 3This is a physical picture of the medical catheter with antibacterial coating of γ-polyglutamic acid electrostatic composite obtained in Examples 1 to 6 of the present invention;

[0030] Figure 4 The infrared spectra of the raw materials γ-polyglutamic acid, lauroyl arginine ethyl ester hydrochloride used in Example 1 of the present invention and the γ-polyglutamic acid electrostatic complex obtained in Example 1;

[0031] Figure 5 This is a physical picture of the γ-polyglutamic acid electrostatic complex obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0032] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0033] The invention provides a gamma-polyglutamic acid electrostatic complex, which is formed by compounding gamma-polyglutamic acid and a positively charged antibacterial surfactant.

[0034] According to the present invention, the γ-polyglutamic acid is preferably obtained by microbial fermentation.

[0035] According to the present invention, the molecular weight of the γ-polyglutamic acid is preferably 10,000 to 2,000,000 Daltons, more preferably 10,000 to 1,000,000 Daltons, further preferably 10,000 to 500,000 Daltons, further preferably 10,000 to 200,000 Daltons, further preferably 10,000 to 100,000 Daltons, further preferably 10,000 to 80,000 Daltons, further preferably 10,000 to 60,000 Daltons, and most preferably 20,000 to 40,000 Daltons; in some embodiments provided by the present invention, the molecular weight of the γ-polyglutamic acid is specifically 20,000 Daltons or 1,000,000 Daltons.

[0036] According to the present invention, the positively charged antibacterial surfactant is preferably one or more of lauroyl arginine ethyl ester hydrochloride, polyhexamethylene biguanide hydrochloride, octadecyl dimethyl benzyl ammonium chloride, hexadecyl trimethyl ammonium chloride and tetradecyl trimethyl ammonium chloride.

[0037] According to the present invention, the mass ratio of the γ-polyglutamic acid to the positively charged antibacterial surfactant is preferably 1:1 to 1:5.

[0038] The γ-polyglutamic acid electrostatic complex provided by the present invention is constructed through electrostatic interaction, and not only has good cell compatibility and blood compatibility, but also has excellent broad-spectrum antibacterial properties, and can be evenly coated on the surface of medical devices with different substrates, shapes and sizes. The combination is stable, and the coating process is universal, which is suitable for solving the current medical device pollution problem, extending its service life, and solving the problem of stable coating on the inner and outer cavity surfaces of complex devices.

[0039] The present invention also provides a method for preparing the above-mentioned γ-polyglutamic acid electrostatic complex, comprising the following steps: S1) providing an aqueous solution of γ-polyglutamic acid; providing an aqueous solution of a positively charged antibacterial surfactant; S2) under stirring, dropwise adding the aqueous solution of the positively charged antibacterial surfactant into the aqueous solution of γ-polyglutamic acid to obtain a precipitate; S3) freeze-drying the precipitate to obtain the γ-polyglutamic acid electrostatic complex.

[0040] The present invention has no particular limitation on the sources of all raw materials, and any raw materials available on the market can be used.

[0041] According to the present invention, the concentration of γ-polyglutamic acid in the aqueous solution of γ-polyglutamic acid is preferably 0.01-0.15 g / mL, more preferably 0.01-0.12 g / mL, further preferably 0.01-0.10 g / mL, further preferably 0.01-0.08 g / mL, and most preferably 0.02-0.05 g / mL.

[0042] According to the present invention, the concentration of the positively charged antibacterial surfactant in the aqueous solution of the positively charged antibacterial surfactant is preferably 0.01 to 0.15 g / mL, more preferably 0.01 to 0.12 g / mL, further preferably 0.01 to 0.10 g / mL, further preferably 0.01 to 0.08 g / mL, and most preferably 0.02 to 0.05 g / mL.

[0043] Under stirring conditions, an aqueous solution of a positively charged antibacterial surfactant is added dropwise to an aqueous solution of γ-polyglutamic acid to obtain a precipitate; the stirring speed is preferably 150 to 500 rpm, more preferably 200 to 450 rpm, and more preferably 200 to 400 rpm; in some embodiments provided by the present invention, the stirring speed is specifically 300 rpm, 200 rpm or 400 rpm; the aqueous solution of the positively charged antibacterial surfactant is preferably added dropwise to the aqueous solution of γ-polyglutamic acid through a peristaltic pump or a dropping funnel; the dropping speed is preferably 10 to 100 mL / min, more preferably 2 0~100mL / min, more preferably 30~100mL / min; in some embodiments provided by the present invention, the dropping speed is specifically 50mL / min, 30mL / min, 80mL / min or 100mL / min; the mass ratio of the γ-polyglutamic acid to the positively charged antibacterial surfactant is preferably 1:1~1:5, more preferably 1:1~1:4, more preferably 1:1~1:3, most preferably 1:1~1:2; after the dropwise addition of the aqueous solution of the positively charged antibacterial surfactant is completed, stirring is preferably continued for 10~40min, more preferably continued for 20~40min.

[0044] The precipitate is preferably centrifuged and washed with water, and then freeze-dried to obtain a γ-polyglutamic acid electrostatic complex; the centrifugal speed is preferably 3000-8000 rpm, more preferably 5000-8000 rpm, and even more preferably 6000-8000 rpm; in some embodiments provided by the present invention, the centrifugal speed is specifically 7000 rpm or 8000 rpm; the centrifugal washing is performed multiple times, preferably until the solution is clear and transparent.

[0045] The present invention provides a method of adding an antibacterial surfactant dropwise into a γ-polyglutamic acid solution to form a milky white precipitate, which is a γ-polyglutamic acid electrostatic complex constructed by electrostatic interaction. The prepared electrostatic complex can be evenly coated on the surface of medical devices of different substrates, shapes and sizes, has stable binding, and has excellent antibacterial properties and good biocompatibility. The present invention solves the problems of the existing medical antibacterial coating preparation process being complicated, high cost, and difficulty in coating the surface of the inner and outer cavities of complex devices with stability and universality.

[0046] The present invention also provides an antibacterial coating, comprising the above-mentioned gamma-polyglutamic acid electrostatic complex.

[0047] The present invention also provides a method for preparing an antibacterial coating, comprising the following steps: S1) dissolving the above-mentioned γ-polyglutamic acid electrostatic complex in an organic solvent to obtain a coating solution; S2) coating the coating solution into a film to obtain an antibacterial coating.

[0048] The above-mentioned γ-polyglutamic acid electrostatic complex is dissolved in an organic solvent to obtain a coating solution; the organic solvent can be an organic solvent well known to those skilled in the art without any special restrictions, and in the present invention, it is preferably one or more of ethanol, methanol and dimethyl sulfoxide; the concentration of the γ-polyglutamic acid electrostatic complex in the coating solution is preferably 0.01-0.1 g / mL, more preferably 0.01-0.08 g / mL, more preferably 0.02-0.06 g / mL, and most preferably 0.02-0.04 g / mL.

[0049] The coating solution is coated to form a film to obtain an antibacterial coating; the coating solution is preferably coated on a substrate to form a film; the substrate is preferably a medical device, more preferably a medical catheter; the material of the substrate preferably includes but is not limited to polymer materials, inorganic materials, metal materials, etc., preferably polyurethane materials; the coating is preferably carried out using a hydrophilic coating dip coater; the coating method is a method well known to those skilled in the art and is not particularly limited, and is preferably spin coating in the present invention; the spin coating time is preferably 10s to 10min, more preferably 30s to 8min, more preferably 1 to 6min, more preferably 1 to 3min, and most preferably 2min; after spin coating, it is preferably air-dried to obtain an antibacterial coating; the air-drying time is preferably 5 to 20min, more preferably 8 to 15min, and more preferably 10min.

[0050] The present invention evaluates the blood compatibility of the γ-polyglutamic acid electrostatic compound antibacterial coating through "GB / T 16886.4 Biological Evaluation of Medical Devices Part 4: Selection of Tests for Interaction with Blood"; evaluates the cell compatibility of the γ-polyglutamic acid electrostatic compound antibacterial coating through "GB / T 16886.5 Biological Evaluation of Medical Devices Part 5: In Vitro Cytotoxicity Test"; and evaluates the antibacterial performance of the γ-polyglutamic acid electrostatic compound antibacterial coating through "GB / T31402-2023 Determination of Antibacterial Activity on the Surface of Plastics and Other Non-porous Materials". The above evaluation results show that the γ-polyglutamic acid electrostatic compound antibacterial coating has good cell compatibility and blood compatibility. At the same time, preferably, the bactericidal rate of the γ-polyglutamic acid electrostatic compound antibacterial coating against Staphylococcus aureus and Escherichia coli is greater than 99%, and has excellent broad-spectrum antibacterial properties. Therefore, the preparation method of the γ-polyglutamic acid electrostatic complex antibacterial coating described in the present invention is simple, and the coating process is universal, which is suitable for solving the current medical device pollution problem, extending its service life, and solving the problem of stable coating on the inner and outer cavity surfaces of complex devices.

[0051] In order to further illustrate the present invention, a γ-polyglutamic acid electrostatic complex provided by the present invention, its preparation method and application are described in detail below in conjunction with examples.

[0052] The reagents used in the following examples are all commercially available.

[0053] Example 1

[0054] Commercially available γ-polyglutamic acid with a molecular weight of 20,000 Daltons was dissolved in water to obtain a 50 g / L γ-polyglutamic acid aqueous solution; commercially available lauroyl arginine ethyl ester hydrochloride was dissolved in water to obtain a 50 g / L lauroyl arginine ethyl ester hydrochloride aqueous solution.

[0055] Under stirring conditions, the prepared lauroyl arginine ethyl ester hydrochloride aqueous solution was added dropwise to the γ-polyglutamic acid aqueous solution through a peristaltic pump to form a milky white precipitate. The stirring speed of the γ-polyglutamic acid aqueous solution was 300rpm / min and the peristaltic pump drop speed was 50mL / min. When the volume ratio of the γ-polyglutamic acid aqueous solution to the lauroyl arginine ethyl ester hydrochloride aqueous solution was 1:2, the dropwise addition was stopped and stirring was continued for 20min. Repeated centrifugation and water washing until the solution was clear and transparent, the centrifugal speed was 7000rpm / min. The milky white precipitate after washing was freeze-dried using a freeze dryer to obtain the γ-polyglutamic acid electrostatic complex.

[0056] The freeze-dried γ-polyglutamic acid electrostatic complex was dissolved in anhydrous ethanol as a coating solution with a concentration of 20 g / L. The coating solution was injected into the dipping tube of the hydrophilic coating dip coater, and the medical polyurethane catheter was placed on the hanging rack of the hydrophilic coating dip coater. The key program was set to rotate and dip for 2 minutes and air dry for 10 minutes, and the γ-polyglutamic acid electrostatic complex antibacterial coating medical catheter was prepared.

[0057] Example 2

[0058] Commercially available γ-polyglutamic acid with a molecular weight of 20,000 Daltons was dissolved in water to obtain a 50 g / L γ-polyglutamic acid aqueous solution; commercially available lauroyl arginine ethyl ester hydrochloride was dissolved in water to obtain a 50 g / L lauroyl arginine ethyl ester hydrochloride aqueous solution.

[0059] Under stirring conditions, the prepared lauroyl arginine ethyl ester hydrochloride aqueous solution was added dropwise to the γ-polyglutamic acid aqueous solution through a peristaltic pump to form a milky white precipitate. The stirring speed of the γ-polyglutamic acid aqueous solution was 300rpm / min and the peristaltic pump drop speed was 30mL / min. When the volume ratio of the γ-polyglutamic acid aqueous solution to the lauroyl arginine ethyl ester hydrochloride aqueous solution was 1:1, the dropwise addition was stopped and stirring was continued for 20min. Repeated centrifugation and water washing until the solution was clear and transparent, the centrifugal speed was 8000rpm / min. The milky white precipitate after washing was freeze-dried using a freeze dryer to obtain the γ-polyglutamic acid electrostatic complex.

[0060] The freeze-dried γ-polyglutamic acid electrostatic complex was dissolved in anhydrous ethanol as a coating solution with a concentration of 10 g / L. The coating solution was injected into the dipping tube of the hydrophilic coating dip coater, and the medical polyurethane catheter was placed on the hanging rack of the hydrophilic coating dip coater. The key program was set to rotate and dip for 4 minutes and air dry for 15 minutes, and the γ-polyglutamic acid electrostatic complex antibacterial coating medical catheter was prepared.

[0061] Example 3

[0062] Commercially available γ-polyglutamic acid with a molecular weight of 1,000,000 Daltons was dissolved in water to obtain a 50 g / L γ-polyglutamic acid aqueous solution; commercially available lauroyl arginine ethyl ester hydrochloride was dissolved in water to obtain a 50 g / L lauroyl arginine ethyl ester hydrochloride aqueous solution.

[0063] Under stirring conditions, the prepared lauroyl arginine ethyl ester hydrochloride aqueous solution was added dropwise to the γ-polyglutamic acid aqueous solution through a peristaltic pump to form a milky white precipitate. The stirring speed of the γ-polyglutamic acid aqueous solution was 300rpm / min and the peristaltic pump drop speed was 100mL / min. When the volume ratio of the γ-polyglutamic acid aqueous solution to the lauroyl arginine ethyl ester hydrochloride aqueous solution was 1:2, the dropwise addition was terminated and stirring was continued for 20min. The solution was repeatedly centrifuged and washed with water until it was clear and transparent, and the centrifugal speed was 7000rpm / min. The milky white precipitate after washing with water was not freeze-dried using a freeze dryer to obtain the γ-polyglutamic acid electrostatic complex.

[0064] The freeze-dried γ-polyglutamic acid electrostatic complex was dissolved in anhydrous ethanol as a coating solution with a concentration of 20 g / L. The coating solution was injected into the dipping tube of the hydrophilic coating dip coater, and the medical polyurethane catheter was placed on the hanging rack of the hydrophilic coating dip coater. The key program was set to rotate and dip for 3 minutes and air dry for 10 minutes, and the γ-polyglutamic acid electrostatic complex antibacterial coating medical catheter was prepared.

[0065] Example 4

[0066] Commercially available γ-polyglutamic acid with a molecular weight of 20,000 Daltons was dissolved in water to obtain a 50 g / L γ-polyglutamic acid aqueous solution; commercially available tetradecyltrimethylammonium chloride was dissolved in water to obtain a 50 g / L hexadecyltrimethylammonium chloride aqueous solution.

[0067] Under stirring conditions, the prepared hexadecyltrimethylammonium chloride aqueous solution was added dropwise to the γ-polyglutamic acid aqueous solution through a peristaltic pump to form a milky white precipitate. The stirring speed of the γ-polyglutamic acid aqueous solution was 200rpm / min and the peristaltic pump drop speed was 30mL / min. When the volume ratio of the γ-polyglutamic acid aqueous solution to the hexadecyltrimethylammonium chloride solution was 1:2, the dropwise addition was terminated and the stirring was continued for 30min. The solution was repeatedly centrifuged and washed with water until it was clear and transparent, and the centrifugal speed was 7000rpm / min. The milky white precipitate after washing with water was not freeze-dried using a freeze dryer to obtain the γ-polyglutamic acid electrostatic complex.

[0068] The freeze-dried γ-polyglutamic acid electrostatic complex was dissolved in anhydrous ethanol as a coating solution with a concentration of 20 g / L. The coating solution was injected into the dipping tube of the hydrophilic coating dip coater, and the medical polyurethane catheter was placed on the hanging rack of the hydrophilic coating dip coater. The key program was set to rotate and dip for 2 minutes and air dry for 10 minutes, and the γ-polyglutamic acid electrostatic complex antibacterial coating medical catheter was prepared.

[0069] Example 5

[0070] Commercially available γ-polyglutamic acid with a molecular weight of 1,000,000 Daltons was dissolved in water to obtain a 50 g / L γ-polyglutamic acid aqueous solution; commercially available tetradecyltrimethylammonium chloride was dissolved in water to obtain a 50 g / L hexadecyltrimethylammonium chloride aqueous solution.

[0071] Under stirring conditions, the prepared hexadecyltrimethylammonium chloride aqueous solution was added dropwise to the γ-polyglutamic acid aqueous solution through a peristaltic pump to form a milky white precipitate. The stirring speed of the γ-polyglutamic acid aqueous solution was 400rpm / min and the peristaltic pump drop speed was 80mL / min. When the volume ratio of the γ-polyglutamic acid aqueous solution to the hexadecyltrimethylammonium chloride solution was 1:2, the dropwise addition was terminated and the stirring was continued for 30min. The solution was repeatedly centrifuged and washed until it was clear and transparent, and the centrifugal speed was 7000rpm / min. The milky white precipitate after washing was freeze-dried using a freeze dryer to obtain the γ-polyglutamic acid electrostatic complex.

[0072] The freeze-dried γ-polyglutamic acid electrostatic complex was dissolved in anhydrous ethanol as a coating solution with a concentration of 20 g / L. The coating solution was injected into the dipping tube of the hydrophilic coating dip coating machine, and the medical polyurethane catheter was placed on the hanging rack of the hydrophilic coating dip coating machine. The key program was set to spin-dip coating for 2 minutes and air-dry for 10 minutes, and the γ-polyglutamic acid electrostatic complex antibacterial coating medical catheter was prepared.

[0073] Example 6

[0074] Commercially available gamma polyglutamic acid with a molecular weight of 1,000,000 Daltons was dissolved in water to obtain a 50 g / L gamma polyglutamic acid aqueous solution; commercially available polyhexamethylene biguanide hydrochloride was dissolved in water to obtain a 100 g / L polyhexamethylene biguanide hydrochloride aqueous solution.

[0075] Under stirring conditions, the prepared polyhexamethylene biguanide hydrochloride aqueous solution was added dropwise to the γ-polyglutamic acid aqueous solution through a peristaltic pump to form a milky white precipitate. The stirring speed of the γ-polyglutamic acid aqueous solution was 200rpm / min and the peristaltic pump drop speed was 100mL / min. When the volume ratio of the γ-polyglutamic acid aqueous solution to the polyhexamethylene biguanide hydrochloride solution was 1:2, the dropwise addition was terminated and the stirring was continued for 40min. The solution was repeatedly centrifuged and washed with water until it was clear and transparent, and the centrifugal speed was 7000rpm / min. The milky white precipitate after washing with water was not freeze-dried using a freeze dryer to obtain the γ-polyglutamic acid electrostatic complex.

[0076] The freeze-dried γ-polyglutamic acid electrostatic complex was dissolved in anhydrous ethanol as a coating solution with a concentration of 20 g / L. The coating solution was injected into the dipping tube of the hydrophilic coating dip coater. The medical polyurethane catheter was placed on the hanging rack of the hydrophilic coating dip coater, and the key program was set to rotate and dip for 2 minutes and air dry for 10 minutes, so that the γ-polyglutamic acid electrostatic complex antibacterial coating medical catheter was prepared.

[0077] Example 7: Evaluation of the antibacterial properties of the γ-polyglutamic acid electrostatic composite antibacterial coating

[0078] The present invention evaluates the antibacterial performance of the γ-polyglutamic acid electrostatic compound antibacterial coating according to "GB / T 31402-2023 Determination of antibacterial activity on the surface of plastics and other non-porous materials". The γ-polyglutamic acid electrostatic compound prepared in Examples 1 to 6 is coated on the surface of a 5cm×5cm sheet substrate material of the same material as the medical catheter described in Examples 1 to 6 as the sample to be tested in the example, and a 5cm×5cm sheet substrate material of the same material without coating treatment is used as a blank control group. The antibacterial rate obtained by the test is shown in Table 1.

[0079] Example 8: Blood compatibility of γ-polyglutamic acid electrostatic composite antibacterial coating

[0080] The present invention evaluates the blood compatibility of the γ-polyglutamic acid electrostatic complex antibacterial coating by "GB / T 16886.4 Biological Evaluation of Medical Devices Part 4: Selection of Tests for Interaction with Blood". Fresh rabbit blood with sodium citrate as an anticoagulant was used for evaluation. The blank control group used the same medical catheter that was not treated with the coating as described in Examples 1 to 6. The negative control group and the positive control group were prepared according to the test standards. The test results are shown in Figure 2. Figure 1 shown.

[0081] Example 9: Cytocompatibility of γ-polyglutamic acid electrostatic composite antibacterial coating

[0082] The present invention evaluates the cell compatibility of the antibacterial coating of the gamma polyglutamic acid electrostatic complex by "GB / T 16886.5 Biological Evaluation of Medical Devices Part 5: In Vitro Cytotoxicity Test". L929 mouse fibroblasts were used as the evaluation cell line. The blank control group used the same medical catheter that was not treated with the coating as described in Examples 1 to 6. The negative control group and the positive control group were prepared according to the test standard. The test results are shown in Figure 2. Figure 2 shown.

[0083] Figure 3 This is a physical picture of the γ-polyglutamic acid electrostatic complex antibacterial coating medical catheter obtained in Examples 1 to 6.

[0084] Example 10: Calculation of the yield of γ-polyglutamic acid electrostatic complex

[0085] The present invention calculates the relative yield of the γ-polyglutamic acid electrostatic complex by dividing the mass of the lyophilized γ-polyglutamic acid electrostatic complex of Examples 1 to 6 by the total mass of the initial monomer feed of Examples 1 to 6. The results are shown in Table 2.

[0086] Example 11: Stability of γ-polyglutamic acid electrostatic complex antibacterial coating

[0087] The present invention coated the gamma polyglutamic acid electrostatic complex prepared in Examples 1 to 6 on the surface of a 5cm×5cm sheet substrate material of the same material as the medical catheter described in Examples 1 to 6 as an example sample, and a 5cm×5cm sheet substrate material of the same material without coating treatment was used as a blank control group. The above samples were soaked in pure water for 30 days, and then the antibacterial properties of the gamma polyglutamic acid electrostatic complex antibacterial coating agent after soaking for 30 days were evaluated according to "Determination of antibacterial activity on the surface of plastics and other non-porous materials GB / T31402-2023", and the results are shown in Table 3.

[0088] Table 1 Antibacterial rate of γ-polyglutamic acid electrostatic composite coating samples against Escherichia coli and Staphylococcus aureus

[0089] Antibacterial rate (%) Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Control group Escherichia coli 99.9 98.2 97.4 97.6 96.5 96.1 0 Staphylococcus aureus 99.9 98.3 97.9 97.5 96.3 97.7 0

[0090] Table 2 Relative yield of γ-polyglutamic acid electrostatic complex

[0091] Grouping Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Yield % 75.5 50.2 52.8 60.2 51.2 61.1

[0092] Table 3 Antibacterial rate of γ-polyglutamic acid electrostatic composite coating samples against Escherichia coli and Staphylococcus aureus after immersion for 30 days

[0093] Antibacterial rate (%) Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Control group Escherichia coli 99.9 96.3 95.7 93.1 94.9 95.0 0 Staphylococcus aureus 99.9 96.1 95.2 93.8 95.2 96.8 0

[0094] It can be seen from the above results that the preparation method of the γ-polyglutamic acid electrostatic complex provided by the present invention is simple and efficient, among which the preferred lauroyl arginine ethyl ester hydrochloride scheme has high yield and stable preparation; the construction method of the γ-polyglutamic acid electrostatic complex coating provided by the present invention is simple and green and environmentally friendly, and no additional treatment of the basement catheter is required. The coating agent can be firmly combined with the inner and outer cavity surfaces of the medical device through hydrophobic interaction by soaking and drying, and is not affected by the shape of the medical device or the raw materials, leaving no dead corners, and can still retain a good antibacterial effect after water soaking for 30 days.

[0095] Example 12: Structural confirmation of γ-polyglutamic acid electrostatic complex

[0096] The raw materials γ-polyglutamic acid, lauroyl arginine ethyl ester hydrochloride and the γ-polyglutamic acid electrostatic complex obtained in Example 1 were analyzed by infrared spectroscopy, and the infrared spectrum thereof was obtained as shown in FIG. Figure 4 As shown. Figure 4 It can be proved that Example 1 was successfully constructed. After ELA and γ-PGA were compounded, the characteristic absorption peaks of the carboxylic acid of γ-PGA (-COO-, 3000-3500cm-1) and the guanidine group of ELA (-C=N, 1640cm-1) appeared simultaneously in the infrared spectrum of γ-PGA-ELA.

[0097] Figure 5 This is a physical picture of the γ-polyglutamic acid electrostatic complex obtained in Example 1 of the present invention.

[0098] In summary, the preparation method of the γ-polyglutamic acid electrostatic complex provided by the present invention is simple, low-cost and high-yield. The steps for forming a coating on the surface of a medical device are simple, and the inner and outer cavity surfaces of the medical device can be evenly covered. The formed γ-polyglutamic acid electrostatic complex coated medical device has excellent antibacterial properties and good biocompatibility, and can be used for antibacterial treatment of the surface of medical devices. It can be used to solve the problems of the complex preparation process, high cost and difficulty in stably coating the inner and outer cavity surfaces of complex devices for existing medical antibacterial coatings.

[0099] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A γ-polyglutamic acid electrostatic complex, characterized in that: It is formed by a complex of γ-polyglutamic acid and a positively charged antibacterial surfactant.

2. The γ-polyglutamic acid electrostatic complex according to claim 1, characterized in that The molecular weight of the γ-polyglutamic acid is 10,000 to 2,000,000 Daltons; The positively charged antibacterial surfactant is selected from one or more of lauroyl arginine ethyl ester hydrochloride, polyhexamethylene biguanide hydrochloride, octadecyl dimethyl benzyl ammonium chloride, hexadecyl trimethyl ammonium chloride and tetradecyl trimethyl ammonium chloride.

3. The γ-polyglutamic acid electrostatic complex according to claim 1, characterized in that The mass ratio of the gamma-polyglutamic acid to the positively charged antibacterial surfactant is 1:1 to 1:

5.

4. A method for preparing a γ-polyglutamic acid electrostatic complex, characterized in that: The following steps are involved: S1) providing an aqueous solution of γ-polyglutamic acid; providing an aqueous solution of a positively charged antimicrobial surfactant; S2) under stirring, adding dropwise an aqueous solution of a positively charged antibacterial surfactant to an aqueous solution of γ-polyglutamic acid to obtain a precipitate; S3) freeze-drying the precipitate to obtain the γ-polyglutamic acid electrostatic complex.

5. The preparation method according to claim 4, characterized in that: The concentration of γ-polyglutamic acid in the aqueous solution of γ-polyglutamic acid is 0.01 to 0.15 g / mL; The concentration of the positively charged antibacterial surfactant in the aqueous solution of the positively charged antibacterial surfactant is 0.01 to 0.15 g / mL.

6. The preparation method according to claim 4, characterized in that: The stirring speed is 150 to 500 rpm; the dripping speed of the aqueous solution of the positively charged antibacterial surfactant is 10 to 100 mL / min; and the stirring is continued for 10 to 40 minutes after the dripping of the aqueous solution of the positively charged antibacterial surfactant is completed.

7. The preparation method according to claim 4, characterized in that: The precipitate is washed with water by centrifugation and then freeze-dried; the centrifugal speed is 3000-8000 rpm.

8. An antibacterial coating, characterized in that: The invention comprises the gamma-polyglutamic acid electrostatic complex described in any one of claims 1 to 3 or the gamma-polyglutamic acid electrostatic complex prepared by any one of the preparation methods of claims 4 to 7.

9. A method for preparing an antibacterial coating, characterized in that: The following steps are involved: S1) dissolving the γ-polyglutamic acid electrostatic complex described in any one of claims 1 to 3 or the γ-polyglutamic acid electrostatic complex prepared by any one of the preparation methods of claims 4 to 7 in an organic solvent to obtain a coating solution; S2) coating the coating solution into a film to obtain an antibacterial coating.

10. The preparation method according to claim 9, characterized in that: The organic solvent is selected from one or more of ethanol, methanol and dimethyl sulfoxide; The concentration of the gamma-polyglutamic acid electrostatic complex in the coating solution is 0.01-0.1 g / mL.

Citation Information

Patent Citations

  • A smart antibacterial coating with good cell compatibility and its preparation method

    CN107854733B

  • Medical catheter surface lubricating antibacterial drug-loaded coating as well as preparation method and application thereof

    CN117442787A

Cited By

  • Binder, preparation method thereof and self-adhesive flexible electrode

    CN121379502A

  • A self-adhering flexible electrode

    CN121379502B

  • Quick-dry antibacterial compound for packaging material as well as preparation method and application of quick-dry antibacterial compound

    CN121549350A

  • Tough polypeptide biological fiber as well as preparation method and application thereof

    CN121781310A